Concept Exploration of Sakinah, Mawaddah, Warahmah as the Foundation of a Muslim Family (Thematic Interpretation Analysis of Q.S Ar-Rum 21)) - Hasan Ismail; Ziadul Ulum Wahid; Alyana Atika Fitri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The family is the most fundamental social institution, playing a crucial role in shaping the quality of individuals and the civilization of society. However, amidst the development of contemporary society, families face various challenges, such as increasing divorce rates, domestic violence, and a weakening of the fulfillment of rights and obligations between family members. These conditions demonstrate the importance of strengthening family values ​​rooted in Islamic teachings. This study aims to comparatively analyze the thoughts of classical and contemporary exegetes regarding the concept of family peace, mawaddah, and raḥmahas a foundation for building a harmonious Islamic family. This research is library research with a thematic interpretation approach (maudhu'i). Primary data sources consisted of the Qur'an and classical and contemporary commentaries, particularly the interpretations of al-Qurthubi, Ibn Kathir, and the thoughts of Quraish Shihab. Secondary data were obtained from books, journal articles, and various relevant literature. The research results show three main findings. First, the Qur'an uses several terminologies to describe the concept of family, such asahl, poison, ‘asyīrah, and arḥām, which show various forms of kinship ties from the nuclear family to the wider social community. Second, classical and contemporary commentators have different emphases in interpreting the concept of peace, mawaddah, and raḥmah, but they all lead to the same goal: to create a harmonious family life full of love and affection. Third, peace, mawaddah, and raḥmah are the three main pillars of the Islamic family, which function to create a balance between rights and obligations, strengthen relations between family members, encourage conflict resolution through deliberation, and build family resilience based on the values ​​of the Qur'an.